Applicability of the dynamic burden of proof’s theory to the Peruvian civil process. Initial draft - Campos Murillo, Walter Eduardo (2012)
This article aims to provide some initial notes in order to establish the suitability of applying the so-called «theory of the evidentiary dynamic loads» in the Peruvian civil process. This theory which provides a means to make more flexible, by way of exception, the rigidity of the general rule of distribution of burden of proof contained in article 196 of the Code of Civil Procedure, constitutes a contribution of the Argentine procedural doctrine to the general theory of the test and that despite not being regulated normatively, has been already received in various fields of our national law. In this line, then established the suitability of adoption at national headquarters, proposes a regulatory text for inclusion in the Peruvian civil procedural law.